2007
DOI: 10.1242/jcs.008607
|View full text |Cite
|
Sign up to set email alerts
|

The C-terminus of ephrin-B1 regulates metalloproteinase secretion and invasion of cancer cells

Abstract: Interaction of the Eph family of receptor protein tyrosine kinases and their ligands, ephrin family members, induces bi-directional signaling via cell-cell contacts. High expression of B-type ephrin is associated with high invasion potential of tumors, however, the mechanism by which ephrin-B promotes cancer cell invasion is poorly understood. We show that interaction of ephrin-B1 with the Eph receptor B2 (EphB2) significantly enhances processing of the extracellular domain of ephrin-B1, which is regulated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 48 publications
3
55
0
Order By: Relevance
“…However, we do not have any evidence at present that ephrin-B1 directly activates the GEF activity of Tiam1, and overexpression of ephrin-B1 did not affect the physical interaction of N-cadherin with b-and a-catenin (data not shown). As one of the mechanisms of ephrin-B1-mediated enhancement of cancer cell invasion, we previously reported that the C-terminus of ephrin-B1 regulates the exocytosis of matrix metalloproteinase (MMP) through the activation of Arf1 GTPase (Tanaka et al, 2007a). We detected elevation of MMP-1 and slight increase in the invasion of collagen by U87MG cells overexpressing ephrin-B1 (supplementary material Fig.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…However, we do not have any evidence at present that ephrin-B1 directly activates the GEF activity of Tiam1, and overexpression of ephrin-B1 did not affect the physical interaction of N-cadherin with b-and a-catenin (data not shown). As one of the mechanisms of ephrin-B1-mediated enhancement of cancer cell invasion, we previously reported that the C-terminus of ephrin-B1 regulates the exocytosis of matrix metalloproteinase (MMP) through the activation of Arf1 GTPase (Tanaka et al, 2007a). We detected elevation of MMP-1 and slight increase in the invasion of collagen by U87MG cells overexpressing ephrin-B1 (supplementary material Fig.…”
Section: Discussionmentioning
confidence: 87%
“…Although investigation of the functions of Eph receptors and ephrins has focused on the development of the vascular and nervous systems, the roles of Eph-ephrin pathways in epithelial cells and cancers have also attracted interest (Batlle et al, 2005;Holmberg et al, 2006;Castaño et al, 2008;Vaught et al, 2008). We previously observed that signaling through ephrin-B1 is involved in the promotion of carcinomatous peritonitis of gastric cancer and pancreas cancer (Tanaka et al, 2007a;Tanaka et al, 2007b;Tanaka et al, 2010).…”
Section: Introductionmentioning
confidence: 97%
“…3F). Because MMP8 is secreted into the medium (Tanaka et al, 2007), we hypothesized that MMP8 could inactivate integrins by binding to the receptor on the 1D). siRNAs inducing downregulation or upregulation of b1-integrin activity in at least four cell lines are indicated with coloured gene IDs in the right column together with the total number of siRNAs affecting 9EG7 or 12G10 binding (z-score ,-1 or .+1) in all of the cell lines studied (numbers in black on the right column).…”
Section: Secondary Screen Validation Of the Integrin Regulatorsmentioning
confidence: 99%
“…Members of the ephrinB family are often overexpressed in cancer cells and are associated with angiogenesis and metastasis (45). Although several studies provide insight into how ephrinB1-mediated reverse signaling contributes to invasion of gastric and pancreas cancer cells (46,47), recent evidence reveals that intracellular domain of ephrinB1 interacts with Dvl and modulates PCP signaling to control cell adhesion and movement in development (48)(49)(50). This opens up the possibility to explore the potential crosstalk between ephrinB and PCP signaling in the context of tumor cell invasion and metastasis.…”
Section: Role Of Pcp Signaling In Tumor Metastasismentioning
confidence: 99%